Amoxicillin and cotrimoxazole-driven dysbiosis disrupted blood cell levels, cytokine balance and induced oxido-nitrosative stress in young mice - Nyabuga, Nyariki James; Cosmas, Kiptoo K.; Kiruki, Silas; Njiri, Olivia A.; Nyambati, Grace K.; Mose, John Mokua; Omwenga Isaac; Isaac, Orina Alfred (Elsevier, 2025)
Amoxicillin and cotrimoxazole are among the most frequently prescribed antibiotics, yet their impact on gut microbiota and systemic physiology, particularly during early life, remains a critical concern. This study investigated the effects of these antibiotics on the gut microbiome and associated physiological and biochemical responses in young male Swiss mice (5 weeks old), serving as a model for infant exposure. Five experimental groups were employed: control, amoxicillin (9.62 mg/kg), cotrimoxazole (15 mg/kg), cotrimoxazole + amoxicillin, and cotrimoxazole + amoxicillin followed by probiotic administration. Parameters assessed included gut microbial composition, hematological indices, organ weights, liver and kidney function, cytokine profiles, oxidative stress markers, and histopathological alterations. Both antibiotics induced marked gut dysbiosis. Cotrimoxazole significantly increased leukocyte, neutrophil, lymphocyte, and monocyte counts, while amoxicillin caused thrombocytosis and cotrimoxazole induced thrombocytopenia; probiotic treatment normalized these effects. Amoxicillin reduced brain glutathione (GSH) levels, whereas cotrimoxazole decreased GSH in both liver and brain. Combined antibiotic exposure exacerbated GSH depletion and elevated nitric oxide (NO) and malondialdehyde (MDA) levels, effects mitigated by probiotics exposure. Co-exposure to cotrimoxazole and amoxicillin upregulated pro-inflammatory cytokines TNF-α and IFN-γ and increased serum markers of hepatic and renal injury (alanine-transaminases, alkaline phosphatases,Aspartate transaminases, creatinine, urea, uric acid). Histopathological analysis confirmed aggravated hepatic and renal damage under combined antibiotic exposure, which was markedlyalleviated by probiotics. These findings demonstrate that amoxicillin and cotrimoxazole disrupt gut microbial balance, eliciting systemic oxidative, organ damage and inflammatory responses. Probiotic intervention confers significant protection, underscoring the need for cautious antibiotic use and microbiota-restorative strategies.
Journal Article
Keywords: Gut micro-biota; dysbiosis; amoxicillin; cotrimoxazole; probiotics